Analysing the environmental factors that influencing papaya disease outbreak - Marliana Azman, 1995- 613486 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2018